circDNMT1 Promotes Malignant Progression of Gastric Cancer Through Targeting miR-576-3p/Hypoxia Inducible Factor-1 Alpha Axis - Li, Hanghang; Cao, Bo; Zhao, Ruiyang; Li, Tian; Xu, Xingming; Cui, Hao; Deng, Huan; Gao, Jingwang; Wei, Bo (Frontiers in Oncology, 2022)
Background: Circular RNAs (circRNAs) regulate multiple malignant behaviors of various types of cancer. The role of circDNMT1, a newly identified circRNA, remains unknown in gastric cancer (GC). This study aimed to elucidate the underlying mechanisms of circDNMT1 in regulating GC progression. Methods: microRNA (miRNA) and circRNA expression was detected by quantitative real-time PCR. Western blotting was performed to measure hypoxia inducible factor-1 alpha (HIF-1α) protein expression. Sanger sequencing, gel electrophoresis and fluorescence in situ hybridization were performed to identify the presence of circDNMT1. The clinicopathological features and overall survival of patients were analyzed based on circDNMT1 expression. The proliferation, migration and invasion of GC cells were determined by cell counting kit-8, 5-ethynyl-2'-deoxyuridine, wound healing and transwell assays. Glycolysis of GC cells was detected based on the levels of glucose uptake, the lactate acid, ATP and pyruvic acid production and the extracellular acidification and oxygen consumption rates. The binding sites between miR-576-3p and circDNMT1 or HIF-1α were predicted by online bioinformatic tools and were validated using RNA pull-down and luciferase reporter assays. Xenograft models were established to determine the effects of the circDNMT1/miR-576-3p/HIF-1α axis on GC growth and metastasis in vivo. Results: circDNMT1 was successfully identified and shown to be overexpressed in GC tissues and cell lines. The expression levels of circDNMT1 were correlated with pathological T stage, pathological TNM stage and shorter survival time of GC patients. circDNMT1 knockdown inhibited the proliferation, migration, invasion and glycolysis of GC cells. circDNMT1 functioned as an oncogenic factor by sponging miR-576-3p. HIF-1α was negatively regulated by miR-576-3p via binding its mRNA 3’ untranslated region. circDNMT1 promoted malignant behaviors and metabolic reprogramming of GC by targeting the miR-576-3p/HIF-1α axis both in vitro and in vivo. Conclusion: These findings demonstrated that circDNMT1 knockdown inhibited GC proliferation, migration, invasion and glycolysis through sponging miR-576-3p/HIF-1α axis. circDNMT1 may be a novel target for GC treatment.